FIVE USM LECTURERS RECEIVE NATIONAL TOP SCIENTISTS AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUALA LUMPUR, 31 October, 2015 – Five Universiti Sains Malaysia (USM) scientists have received prestigious awards as the Top Research Scientists Malaysia (TRSM) from the Academy of Sciences Malaysia (ASM) for significant contributions within their respective fields of research.